(untitled) (Economics and region, 2023)
The purpose of this study is to determine how the education workers in Azerbaijan are affected by the Covid-19 pandemic, to investigate the changes in teachers’ behavior, and to find solutions for the problems caused by distance education. The information base of the research includes literature, internet resources, articles and magazines written in English, Turkish and Azerbaijani languages. Research and recommendations of international organizations were also used. For the analyzing data, a mixed method was used, in which qualitative and quantitative research methods were used together. According to previous researches, combining quantitative and qualitative methods in mixed method design will give more effective results and help in comprehensive analysis of the problem. It is known that despite the great advantages of the distance education system, the rapid transition to this system had a negative impact on teachers and the education system in general. Distance learning has led to teachers spending more time online. Processes such as teaching process, assessment of students, dealing with students, learning how to use online education platforms in a short time, communication with parents and providing support to them have been implemented online. Online implementation of such processes has created problems for teachers such as technostress, psychological stress, decreased motivation, and lower job satisfaction. According to the results of the research, the majority of teachers support the joint application of distance and traditional education systems, they positively evaluate distance education only in terms of eliminating the time and space factor in education, and continuing education in crisis situations, and increasing students’ ICT skills. Education workers note the importance of the joint support of the Ministry of Education, students’ parents and school leaders to solve the problems that have arisen.